Analisis Pengaruh Kepemimpinan Kepala Sekolah, Disiplin Kerja Guru dan Profesionalisme Guru Terhadap Kinerja Guru Sekolah Menengah Pertama Negeri 15 Kota Palembang - Agung Indriansyah (Jurnal Manajemen, 2022)
AGUNG INDRIANSYAH, Influence Analysis Principal Leadership, Work Discipline Teacher And Teacher Performance Against Teacher Professionalism Junior High School 15 Palembang, under the guidance of Prof. Dr.. H. Hosni Suradji and Drs.H.Rustam Effendi,M.Sc. This study aims to examine how the influence of Principal Leadership, Work Discipline Teacher and Teacher Professionalism on the Performance of State Secondary School Teachers 15 Palembang. Implementation research for 4 (four) months including the design, conduct and reporting of research result. Respondents in this study were 30 junior high school teacher 15 Palembang. The data obtained in this study were derived from answers - answers to questionnaires distributed to each respondent. The analysis model used is multiple linear regression model in which the variables used in this study is the independent variable: Principal Leadership (X1), Work Discipline Teacher (X2), Professional Teacher (X3) and the Teacher Performance (Y) as the Dependent variable. In accordance with the results of statistical analysis, it is common - the same independent variables and partial Principal Leadership, Teacher Work Discipline and Professional Teacher has an influence on Performance Junior High School Teacher 15 of Palembang.